A Note on Forestry in West Bengal - Mitra, S. N . (Indian Forester, 1949)
No material amount of grazing can be expected from the existing reserved forests. The entire Sundarbans which forms 61.5 per cent of these forests, besides being too swampy, yield practically no fodder. The North Bengal forests are the only timber reserves we have got and these are also too precious as protection forest to be endangered in any way by grazing. The incidence of grazing in these forests, as given free to the cattle of the forest villagers and to those of the contractors and purchasers engaged on extraction of forest produce, is already pretty high. No more grazing can be allowed there without serious deteriment to those forests. As a matter of fact, not to speak of admitting more grazing, it has always been found necessary to keep under a strict limit the number of the resident cattle and to prevent illicit grazing by outside cattle as much as possible. The new timber-reserves, if any be created, can also furnish little or no grazing as it is totally incompatible with the creation, maintenance and regeneration of timber-producing forests. The new firewood-reserves, as and when created and if properly managed, can furnish perpetual and good grazing over one-third to one-half of their total area, the actual proportion being determined by the rate of growth of the crop and the consequent rotation. As our land-resources stand, we cannot possibly have sufficient firewood-cum-pastures-reserves or separate pastures to give adequate accommodation to the existing large stock of cattle and buffaloes for grazing. Solution of the acute problem of fodderfamine will, therefore, demand;- (i) Elimination of all useless cattle and its replacement by superior stock so that we can meet our requirements with a greatly reduced number of them and consequently have less mouths to feed. (ii) Encouraging the practice of stall-feeding cattle with dry and green fodder and silage. (iii) Increasing the quantity and quality of fodder by systematic cultivation of grasses and legumes of high food value. Such agricultural crops , cereal or cash, which deplete the soil should be rotated with legumes which replenish the fertility of the soil and at the same time furnish rich fodder.